Organizational and Economic Instruments of Investment and Innovation Providing Restructuring of the Enterprise - Ð’ielova, Alla; Orlovska, Olexandra; Zhuravska, Natalia; Kochedikova, Alona (International Journal of Engineering and Technology, 2018)
The article deals with the organizational and economic tools of innovative development of enterprises, it is determined that one of the main factors in ensuring a balanced functioning of the economy and increasing the competitiveness of industrial enterprises in world markets is the achievement of the effectiveness of the formation and introduction in practice of an effective restructuring management system, which is to effectively involve investment resources and innovation potential. It was investigated that achievement of the equilibrium of functioning can not be solved without systematic research of the effectiveness of management of restructuring processes and the development of an objective method for estimating and forecasting the effectiveness of restructuring management with adaptation to modern economic conditions based on international experience. The interdependence and interconnection of key areas of enterprise restructuring according to the main objects of application of efforts have been determined, the three levels of management structure restructuring have been constructed according to the priority of the implementation of the target functionalities of its functional elements, and the feasibility of conducting restructuring changes for increasing the production of innovative products type and their advantages for both the consumer, and for the state.Â Â Â